Systematic Bibliometric Research Trend of Text Mining on Product Comments in Business Ecosystem - Gifthera Dwilestari; Fadhil Muhammad Basysyar (Ikatan Ahli Informatika Indonesia, 2024)
The business ecosystem represents a new paradigm that has gained considerable attention among researchers and practitioners. Despite its popularity, systematic literature reviews utilizing bibliometric analysis within this context remain sparse. This study aims to conduct a comprehensive bibliometric and visualization analysis of business ecosystem research, focusing on the impact of text mining on product comments. Employing VOSviewer for visualization, the study evaluates 95 scientific articles indexed in Scopus quartiles Q1 to Q4 from the Scopus database over the last decade (2001-2024). The bibliometric analysis identifies the most productive publishers, the evolution of scientific articles, and citation patterns. Visualization with VOSviewer reveals prevalent terms in titles and abstracts, author collaboration networks, and assists in identifying novel and underexplored topics within the business ecosystem. The findings provide valuable insights for researchers and practitioners, highlighting key trends and potential research gaps, thus contributing to the advancement of knowledge in the field.